Variability in iron, zinc and phytic acid content in a worldwide collection of commercial durum wheat cultivars and the effect of reduced irrigation on these traits - Magallanes-Lopez, Ana Maria; Hernandez-Espinosa, Nayeli; Velu, Govindan; Posadas-Romano, Gabriel; Ordonez-Villegas, Virgina Maria Guadalupe; Crossa, José; Ammar, Karim (Elsevier, 2017)
Diets very rich in cereals have been associated with micronutrient malnutrition, and the biofortification of them, has been proposed as one of the best approaches to alleviate the problem. Durum wheat is one of the main sources of calories and protein in many developing countries. In this study, 46 durum varieties grown under full and reduced irrigation, were analyzed for micronutrients and phytate content to determine the potential bioavailability of the micronutrients. The variation was 25.7-40.5 mg/kg for iron and of 24.8-48.8 mg/kg for zinc. For phytate determination (0.462 to 0.952 %), a modified methodology was validated in order to reduce testing costs while speeding up testing time. Variation was detected for phytate:iron and zinc molar ratios (12.1-29.6 and 16.9-23.6, respectively). The results could be useful to generate varieties with appropriate levels of phytate and micronutrients, which can lead to the development of varieties rich in micronutrients to overcome malnutrition.